2010 3dtv-Conference: The True Vision - Capture, Transmission and Display of 3D Video 2010
DOI: 10.1109/3dtv.2010.5506511
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of depth compression and view synthesis distortions in multiview-video-plus-depth coding systems

Abstract: Several quality evaluation studies have been performed for videoplus-depth coding systems. In these studies, however, the distortions in the synthesized views have been quantified in experimental setups where both the texture and depth videos are compressed. Nevertheless, there are several factors that affect the quality of the synthesized view. Incorporating more than one source of distortion in the study could be misleading; one source of distortion could mask (or be masked by) the effect of other sources of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Though, the subjective scores correlated the VSSIM scores. Recently, [6] reconsidered the synthesis quality evaluation framework. The authors showed the importance of the chosen reference for synthesis quality evaluation: they pointed out the fact that depending on the chosen reference (original view or control synthesis, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Though, the subjective scores correlated the VSSIM scores. Recently, [6] reconsidered the synthesis quality evaluation framework. The authors showed the importance of the chosen reference for synthesis quality evaluation: they pointed out the fact that depending on the chosen reference (original view or control synthesis, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, there are a lot of distortion sources such as slightly different camera response function, exposure time, and lighting condition among multiview images. It has also been shown in [34] that the distortion introduced by VSRS widely masks those due to depth map compression, which can result in a misleading study in order to justify the effectiveness of depth compression.…”
Section: Resultsmentioning
confidence: 99%
“…In the past, a detailed evaluation of multi-view video coding schemes has been made, mainly focusing on the extension of the popular H.264/AVC coding standard [4]. More recently, some preliminary evaluation of depth map compression performance was made in [5,6]. While [5] evaluates the coding distortion of two depth map coding solutions, notably H.264/AVC and a depthimage modeling approach, [6] assesses the performance of the H.264/AVC video coding standard using three PSNR-based quality metrics.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, some preliminary evaluation of depth map compression performance was made in [5,6]. While [5] evaluates the coding distortion of two depth map coding solutions, notably H.264/AVC and a depthimage modeling approach, [6] assesses the performance of the H.264/AVC video coding standard using three PSNR-based quality metrics. However, in both studies, only the H.264/AVC coding standard is considered and uncoded original views (texture) are used at the decoder side which is not a very realistic situation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation